Current state of the problem of chronic alcoholism, new approaches in its correction (literature review) - E. V. Filippova; K. E. Bukin; A. D. Dyachkova; E. V. Sosnovskaya (Лечащий Врач, 2022)
Alcoholic disease is a disease in which a long-term repeated intoxication with ethanol plays a decisive role, provoking the occurrence of morphological and functional changes in the organs and systems of the body. To select a scheme and successive stages of treatment of chronic alcoholism and withdrawal syndrome, it is necessary to understand the pathogenesis of the disease and the principles of action of the drugs used, in order to determine the points of application of therapy, as well as the stages of pharmacotherapy. The paper presents an overview of articles devoted to the problems of chronic alcoholism. A significant amount of the material used was collected by searching for scientific publications and research by foreign and domestic authors. It is noted in the literature that chronic alcoholism is accompanied by damage to almost all vital organs and systems, which leads to complications, and can also cause the development of alcohol withdrawal. Most of the authors, to one degree or another, pay attention to the predominant damage of the cardiovascular system, probably associated with an increased level of catecholamines during regular alcoholization, to which the myocardium reacts first. It is with this phenomenon that the mortality of patients suffering from chronic alcoholism is associated, not only from complications from the cardiovascular system, but also from manifestations of an iatrogenic nature caused by the use of depressants in the treatment of such patients that can cause acute heart failure against the background of myocardial damage by alcohol. The authors associate these complications with the need to use drugs of depressing groups in high doses, as a result of which they begin to show a toxic effect, primarily on the cardiovascular system. According to modern experimental studies, a decrease in the toxic effect of depressants included in the protocols for the treatment of chronic alcoholism was revealed when used in combination with a representative of the class of antioxidants on laboratory animals. In addition, the dependence of the effectiveness of the therapy on the time of day at which medications are taken has been experimentally established, which dictates the need to take into account the chronopharmacology factor when prescribing therapy.